Eksistensi BUMN sebagai Korporasi yang Dikuasai oleh Negara - Agus Adhari (Dialogia Iuridica, 2015)
Indonesian state owned enterprises (BUMN) is a corporation, which is a large part or entirely (stoke) controlled by the state. State presents through Indonesian state-owned enterprises in order to carry out the mandate of Article 33 of UUD 1945, where the economic sectors that dominate the life of people controlled by the state. BUMN as a corporation must be clarified, either its functions or its objectives. Article 4 (1) of Law No 19 of 2003 on state enterprises, should be explanatory, that the state is only the owners of capital, and no longer consider BUMN as a state institution funded by the state. BUMN as a corporation should be clarified either in law or on the level of implementation. The number of government’s intervention in BUMN, shows that the country is not ready to have a corporation in order to carry out the mandate of Article 33 of the Constitution of 1945. It makes BUMN intervened by political interests, rather than corporate interests.